Eksperimen Pelat Beton Bertulang Bambu Ampel - Rima Siti Rohimah; Eko Walujodjati (Institut Teknologi Garut, 2022)
Indonesia's need for roads and access to buildings is increasing, but this is not matched by balanced economic growth. Therefore, a low cost alternative is sought to make the structure strong and light. As an alternative to steel reinforced concrete slabs, non-structural components, etc., ampel bamboo reinforced concrete slabs are an effective combination. The ampel bamboo to be used is bamboo with an age of more than one year, then this bamboo will be shaped to resemble plain iron reinforcement with a diameter of 8 mm. Then the test was carried out with a treatment age of 28 days. This study aims to determine the effect of haur bamboo on the feasibility of concrete in terms of one-way flexural strength and tensile strength of ampel bamboo itself. This research was conducted using the experimental method and three specimens were made for one-way flexural strength testing with the dimensions of the specimens (10x20x60) cm. From the results of the study it can be concluded that the average tensile strength of ampel bamboo is 396.10 MPa and meets the standard of plain iron reinforcement, namely a minimum tensile strength of 350 MPa and the flexural strength capacity of concrete slabs obtained by replacing iron reinforcement using ampel bamboo is 1, 16 KNm.